Respuesta :
Answer:
-28
Step-by-step explanation:
Simplifying
3m + 6 + -2m = -22
Reorder the terms:
6 + 3m + -2m = -22
Combine like terms: 3m + -2m = 1m
6 + 1m = -22
Solving
6 + 1m = -22
Solving for variable 'm'.
Move all terms containing m to the left, all other terms to the right.
Add '-6' to each side of the equation.
6 + -6 + 1m = -22 + -6
Combine like terms: 6 + -6 = 0
0 + 1m = -22 + -6
1m = -22 + -6
Combine like terms: -22 + -6 = -28
1m = -28
Divide each side by '1'.
m = -28
Simplifying
m = -28